05 ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI JERUK PAMELO (Studi Kasus di Kelurahan Attang Salo Kecamatan Ma’rang Kabupaten Pangkep) - Jurnal Agribis; Urianti Urianti; Arifin Arifin; Mohammad Anwar Sadat (Jurnal Agribis, 2017)
The purpose of this study was to determine the amount of production and farming income of pummelo oranges in Attang Salo Village, Ma'rang District, Pangkep Regency. This research will be conducted in Tanete Village, Simbang District, Maros Regency. Knowing the factors that influence the production of pemelo citrus farming in Attang Salo Village, Ma'rang District, Pangkep Regency. And knowing the factors that affect the income of pemelo citrus farming in Attang Salo Village, Ma'rang District, Pangkep Regency. The research activity was carried out in Attangsalo Village, Ma'rang District, Pangkep Regency. To determine the factors that influence farmer motivation, the data analysis used is income analysis and multiple linear regression analysis. Based on the results of research and discussion, the results of the study are that the average production and income of citrus farmers in Attang Salo Village, Ma'rang District, Pangkep Regency is a production of 1,641 fruits and an income of Rp. 4,197,591.11. The variables of land area, labor and organic fertilizers had a significant effect on the production of citrus plants. And the variables of land area, labor wages and NPK fertilizer have a significant effect on citrus farming income.